2020
DOI: 10.3390/jcm9092949
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Combination of Myo-Inositol, Alpha-Lipoic Acid, and Folic Acid on Oocyte Morphology and Embryo Morphokinetics in non-PCOS Overweight/Obese Patients Undergoing IVF: A Pilot, Prospective, Randomized Study

Abstract: Herein we aimed at assessing whether Myo-Inositol (MI), Alpha–Lipoic acid (ALA), and Folic acid (FA) could improve oocyte quality and embryo development in non-PCOS overweight/obese women undergoing IVF. Three hundred and twenty-four mature oocytes were obtained from non-PCOS overweight/obese patients, randomized to receive either MI, ALA, and FA (MI + ALA + FA group, n = 155 oocytes) or FA alone (FA-only group, n = 169 oocytes). Oocytes were examined using Polarized Light Microscopy to assess morphological fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Inositols are effective and universal fertility-improving compounds that can be used for the treatment of obese patients without PCOS [ 157 ], lean PCOS patients without IR [ 158 ] and obese PCOS patients [ 159 ]; however, other research suggests that the inositol effect is IR-dependent [ 160 ].…”
Section: Pcos Treatments: Classical and Modern Mitochondria–oriented Approachesmentioning
confidence: 99%
“…Inositols are effective and universal fertility-improving compounds that can be used for the treatment of obese patients without PCOS [ 157 ], lean PCOS patients without IR [ 158 ] and obese PCOS patients [ 159 ]; however, other research suggests that the inositol effect is IR-dependent [ 160 ].…”
Section: Pcos Treatments: Classical and Modern Mitochondria–oriented Approachesmentioning
confidence: 99%
“…ALA is a well-established treatment for neuropathic symptoms and dysfunctions in distal symmetric polyneuropathy (DSP) and type 2 diabetes [33,34].…”
Section: Clinical Pharmacologymentioning
confidence: 99%
“…Alpha-lipoic acid exhibits immunomodulatory and antioxidant activity, which improves embryo implantation and stimulates the production of local mediators that facilitate implantation. For instance, a study by Canosa et al [5] showed that the intake of inositol, alpha-lipoic and folic acids had a beneficial effect on the molecular organization of zona pellucida during follicle maturation, which is physiologically rearranged during oocyte maturation [4].…”
Section: Discussionmentioning
confidence: 99%